Multiplex Quantitative PCR for the Detection of Bacteria Associated with Huanglongbing ‘Candidatus Liberibacter asiaticus,’ ‘Ca. L. americanus,’ and 16Sr IX Group Phytoplasma - Martins, Elaine C. [UNESP]; Teixeira, Diva C.; Coletti, Daniela A.B.; Wulff, Nelson A. [UNESP] (Scientific Societies, 2025)
The occurrence of ‘Candidatus Liberibacter’ spp. and ‘Ca. Phytoplasma’ spp. associated with blotchy mottle symptoms poses challenges to huanglongbing (HLB) diagnosis using molecular techniques. The ability to detect multiple targets simultaneously and specifically is a key aspect met by quantitative PCR (qPCR). A set of primers and hydrolysis probes useful in either single or multiplex reactions for the detection and quantification of HLB-associated bacteria were developed. Sequences from conserved genes of the ribosomal proteins for Liberibacter and phytoplasma circumvent the lack of specificity and cross-reactivity problems related to 16Sr DNA gene amplification, allowing precise and specific detection of HLB-associated bacteria in citrus and in the Liberibacter vector, Diaphorina citri. The triplex reaction exhibited high quality and precision as a robust tool for quantifying ‘Ca. L. asiaticus’ (CLas), ‘Ca. L. americanus’ (CLam), and 16Sr IX phytoplasma. Triplex qPCR showed consistent results and comparable sensitivity to the ribonuclease reductase test, although quantification cycle (Cq) values were higher when compared with 16SrDNA qPCR. Detection tests using field samples indicate that the qPCR triplex can identify HLB-associated bacteria in samples with varying levels of symptoms, ranging from typical to asymptomatic. Assessment of field samples from growers indicated more than 78.6% had Cq lower than 35.0, below the cutoff established for qPCR reactions used in this work. qPCR triplex is a safe, specific, and sufficiently sensitive technique for detecting CLas, CLam, and 16Sr IX phytoplasma simultaneously, in both citrus and D. citri samples. Its application is of importance in assisting growers in making decisions for HLB management.
Keywords: citrus; D. citri; greening; Huanglongbing; Liberibacter; multiplex; Phytoplasma; psyllid; qPCR; quantification